2011
DOI: 10.1200/jco.2010.30.1622
|View full text |Cite
|
Sign up to set email alerts
|

Development and Measurement of Guideline-Based Indicators for Patients With Non-Hodgkin's Lymphoma

Abstract: In the Netherlands, almost all indicators for NHL needed improvement. This should be evaluated in other countries as well. International efforts should be undertaken to improve the quality of care of this often curable malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 30 publications
1
49
1
Order By: Relevance
“…An analysis from the National Lymphocare Study exploring the patterns of use and the effectiveness of different treatment modalities in FL [1,19] revealed that one third of stage I FL patients were treated with radiotherapy alone, similar to other retrospective studies [16,18], and to our study. This lack of compliance with the guidelines could be due to patient and tumor related factors, making the adherence to guidelines low compared to other malignancies [19,25]. In the present study, the use of systemic therapy was more frequent in patients with adverse prognostic factors, such as an intermediate or high FLIPI score, or in those with more disseminated disease and high grade histology, a feature also observed in the subgroup of patients diagnosed with stage I FL.…”
Section: Discussioncontrasting
confidence: 44%
“…An analysis from the National Lymphocare Study exploring the patterns of use and the effectiveness of different treatment modalities in FL [1,19] revealed that one third of stage I FL patients were treated with radiotherapy alone, similar to other retrospective studies [16,18], and to our study. This lack of compliance with the guidelines could be due to patient and tumor related factors, making the adherence to guidelines low compared to other malignancies [19,25]. In the present study, the use of systemic therapy was more frequent in patients with adverse prognostic factors, such as an intermediate or high FLIPI score, or in those with more disseminated disease and high grade histology, a feature also observed in the subgroup of patients diagnosed with stage I FL.…”
Section: Discussioncontrasting
confidence: 44%
“…A recent analysis of guideline adherence in patients from the Netherlands with lymphoma suggested that both patient-and tumor-related factors impede adherence to guidelines, and the need to improve care guidelines in lymphoma is higher than for several other tumor types. 7 A comprehensive approach that targets the physician, team members, hospitals, and care environment is required to improve guideline adherence. 8 However, our data question whether XRT, which is the historical standard, is the best choice and whether it has any impact on outcomes in this group of patients compared with other treatment modalities, including observation.…”
Section: Discussionmentioning
confidence: 99%
“…However, active implementation is needed to increase adherence as publication and dissemination is not sufficient [9]. In France, as in other European countries, a national cancer plan has been implemented and adherence is promoted as an important step to enhancing quality of cancer care [10].…”
Section: Introductionmentioning
confidence: 99%